FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA PERKEBUNAN SAWIT PT. KEDATON MULIA PRIMAS JAMBI TAHUN 2017 - Yenni, Melda (Universitas Tribhuwana Tunggadewi, 2020)
The increasing of growth of any oil palm crop is not accompanied by safe behavior in the use of PPE in oil palm plantations. This is evident from most workers who do not work safely by not using PPE when they accomplished their activities. This study aims to determine of the use of Personal Protective Equipment (PPE) to workers in oil palm plantations. This is a quantitative research with cross sectional.The study population was all plantation workers totaling 77 workers and the sampling technique using total sampling method from the total total population of 77 workers. The results showed that the behavior of using PPE was in the bad category at 61.0%. Knowledge (p = 0.031), attitude (p = 0.001) and training (0.018) are variables that have a relationship with the use of PPE. Conclusions show that most workers know about the use of PPE but workers do not believe that one way to reduce the risk of workplace accidents is by using personal protective equipment and most of them have said that they have attended training in the use of personal protective equipment.